2016
DOI: 10.1051/0004-6361/201629052
|View full text |Cite
|
Sign up to set email alerts
|

Variability of stellar granulation and convective blueshift with spectral type and magnetic activity

Abstract: Context. In solar-type stars, the attenuation of convective blueshift by stellar magnetic activity dominates the RV (radial velocity) variations over the low amplitude signal induced by low mass planets. Models of stars that differ from the Sun will require a good knowledge of the attenuation of the convective blueshift to estimate its impact on the variations. Aims. It is therefore crucial to precisely determine not only the amplitude of the convective blueshift for different types of stars, but also the depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
92
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 68 publications
17
92
1
Order By: Relevance
“…Granulation in the photosphere is a manifestation of thousands of rising warm gas cells surrounded by a network of descending cool gas (Del Moro 2004). Granulation flow velocities are km s −1 , leading to a net blueshift of hundreds of m s −1 in full-disk observations of Sun-like stars (Meunier et al 2017;Gray 2009). The granulation blueshift depends on stellar properties and for a given star varies by meters per second as photospheric magnetic fields evolve over timescales shorter than a few days (Dumusque et al 2011;Lefebvre et al 2008).…”
Section: Photospheric Velocitiesmentioning
confidence: 99%
“…Granulation in the photosphere is a manifestation of thousands of rising warm gas cells surrounded by a network of descending cool gas (Del Moro 2004). Granulation flow velocities are km s −1 , leading to a net blueshift of hundreds of m s −1 in full-disk observations of Sun-like stars (Meunier et al 2017;Gray 2009). The granulation blueshift depends on stellar properties and for a given star varies by meters per second as photospheric magnetic fields evolve over timescales shorter than a few days (Dumusque et al 2011;Lefebvre et al 2008).…”
Section: Photospheric Velocitiesmentioning
confidence: 99%
“…For Sun-like stars with low activity, suppression of convective blueshift due to photospheric plage (hereafter RV conv ) dominates over the wavelength-independent photometric effects due to spots, or RV shifts induced by Earth-like exoplanets (Meunier et al 2010b;Dumusque et al 2014;Haywood et al 2016) (hereafter RV sppl ). Meunier et al (2017a) (hereafter M17) have developed one model to isolate RV conv contributions based on the observed non-linear relationship between relative depths and absolute RV blueshifts of spectral lines of a given species (here neutral iron) driven by plasma flow in granules, as described in Gray (2009);Reiners et al (2016); Meunier et al (2017b); Gray & Oostra (2018). The exact physical origin of this observed correlation is non-trivial: a correct description of spectral line formation necessitates the summation of many different line profiles, each formed at different depths in the photosphere, and requires a full threedimensional treatment (e.g., see Nordlund et al 2009;Stein 2012;Cegla et al 2013;Bergemann et al 2019 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that stars with identical spectral types but different levels in small-scale convection such as granulation (either on average or its temporal variability) impacting the convective blueshift, such as that derived by Meunier et al (2017), will give a similar α if the differential velocity shift of spectral lines is universal, as pointed out by Gray (2009), because the shape of the differential velocity shift will be similar to that of Eq. 3.…”
Section: Line Set Choicementioning
confidence: 90%
“…Here we consider that α may be known with a certain uncertainty; α could indeed be estimated independently from the RV series, for example by analyzing the spectra, as done by Gray (2009), Meunier et al (2017, either for the star being studied or for the spectral type corresponding to it, or by magnetohydrodynamic numerical simulations of convection associated with the production of spectra for various spectral types (such as those produced by e.g., Ramírez et al, 2009, Chiavassa et al, 2011, Allende Prieto et al, 2013, Magic et al, 2014) that would then be analyzed as observed spectra. Such techniques to derive α, independent of the RV time series, have not yet been fully developed, but may in the future allow for a complementary computation of α.…”
Section: Case 1: α Known With a Given Uncertaintymentioning
confidence: 99%